Acoustical Design of the Blue Whale Auditorium in Buenos Aires - Basso, Gustavo Jorge (2019)
The "Blue Whale" Auditorium in Buenos Aires opened in 2015. Designed to be the headquarters of the National Symphony Orchestra of Argentina, its goal was to become the city's main space for symphonic music. The architectural program posed several challenges from an acoustic point of view, as 2,000 people had to be accommodated in a square space into which none of the usual architectural typologies fit properly. It was decided, therefore, to place in this space an "ad-hoc" hall, whose shape is far from traditional. The design centred around three main premises: to achieve an enveloping acoustic field, by generating a large number of lateral reflections within the Haas limit; to establish an adequate triple-slope reverberation decay; and to combine reflective and diffusing surfaces to attain a similar acoustic field through the entire audience area. This work details the design process of the Auditorium, during which the final shape was deduced from the established acoustic premises.